ANTIBACTERIA ACTIVITY OF PAPUAN ANT-NEST (MYRMECODIA PENDANSL.M. Perry) ETHANOL EXTRACT AGAINST SHIGELLA DYSENTERIAE - Kusuma, Arif Satria; Kusuma, Sri Agung Fitri; Sulistiyaningsih, Sulistiyaningsih (Asian Journal of Pharmaceutical and Clinical Research, 2017)
This research aimed to determine antibacteria activity of ant-nest extract against Shigella dysenteriae and to determine its Minimum Inhibitory Concentration (MIC) â€“ Minimum Bactericidal Concentration (MBC) range of concentration. S. dysenteriae continues to be a major health problem in Indonesia, which usually leads to death, due to diarrhoea and dysentery, predominantly in children below the age of 5. Bacterial invasion of the colonic epithelium leads to severe inflammation together with bacterial dissemination generates abscesses and ulcerations. Myrmecodia pendans, also locally known by indigenous Papuans as ant-nest is native to Southeast Asia. This tropical plant has proven to be rich in bioactive constituents and highly valued as an alternative choice for cancer/tumor treatments and an efficacious herbal drug to prevent and cure diarrhea.Ant-nest dried plant were obtained from Wamena, Papua. The extract was obtained using maceration method with 70% ethanol, from 500.42 g dried plant we can obtain 77.47 g dry extract (15.48% rendement). Phytochemical screening result showed that the ethanol extracts of ant-nest contains metabolites such as alkaloids, flavonoids, tanins, saponins, and steroids/terpenoids. Antibacteria activity test were then performed by using perforated agar method with various extract concentration (10, 20, 40, and 60 % (g/ml)). Largest inhibition zone was shown by 60% extract concentration with 1.74 cm diameter. MIC-MBC concentration determinated by using microdilution method. The result shown that concentration of MIC â€“ MBC lays in range of 14 â€“ 16 % (g/ml). Â